State-Owned Enterprises (SOES): The Ability And The Feasibility During The Industrial Revolution 4.0. - Zahari, Muhammad; Harmadi, Ashur; Mustika, Mustika; Manullang, Sardjana Orba; Dewi, Dyah Handayani (Jurnal Manajemen Industri dan Logistik, 2023)
The goal of this study was to identify the key elements that would help design procedures for improving corporate images in urban company. The studies were quantitative and used observation, questioning, and interviews as three key sources of data. With a path coefficient of 0.94, the results show that the Customer Satisfaction variable and the Corporate Image variable are positively correlated. Corporate Image increases by 0.94 units or has an impact of 0.94 units on the increase in Corporate Image if Customer Satisfaction increases. The overall impact of service quality on client satisfaction at PDAM Tirta Indragiri is 67.86 percent. Product quality, such as water clarity, colour, and odour, is the customer satisfaction dimension with the lowest value, in line with the distribution performance issue. Therefore, to improve water quality and distribution, quality control management must be planned, implemented, and carried out systematically and continuously.